Existence of positive periodic solutions for scalar delay differential equations with and without impulses - Faria, Teresa (2019)
The paper is concerned with a broad family of scalar periodic delay differential equations with linear impulses, forwhich the existence of a positive periodic solution is established under very general conditions. The proofs rely on fixed point arguments, employing either the Schauder theorem or Krasnoselskii fixed point theorem in cones. The results are illustrated with applications to an impulsive hematopoiesis model or generalized Nicholson’s equations, among other selected examples from mathematical biology. The method presented here turns out to be very powerful, in the sense that the derived theorems largely generalize and improve other results in recent literature, even for the situation without impulses.